2016
DOI: 10.1080/14760584.2016.1236689
|View full text |Cite
|
Sign up to set email alerts
|

The RTS,S/AS01 malaria vaccine in children 5 to 17 months of age at first vaccination

Abstract: The RTS,S/AS01 malaria vaccine received a positive scientific opinion from the European Medicines Agency in July 2015. The World Health Organization recommended pilot implementation of the vaccine in children at least 5 months of age according to an initial 3-dose schedule given at least 1 month apart, and a 4th dose 15-18 months post-dose 3. Clinical trials and mathematical modeling demonstrated that the partial protection provided by RTS,S/AS01 against malaria has the potential to provide substantial public … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 50 publications
0
49
0
3
Order By: Relevance
“…We have previously reported that a 4-dose regimen of RTS,S/ AS01 was efficacious and provided the strongest benefit in terms of impact against clinical and severe malaria in children aged 5-17 months at the time of the first vaccination. 16 Additionally, reductions in overall hospital admissions, admissions because of malaria, severe anemia, and the need for blood transfusion in children were observed. We also previously reported an increased risk of febrile convulsions in children vaccinated with RTS,S/AS01 in our large doubleblind, randomized, phase III trial in SSA.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that a 4-dose regimen of RTS,S/ AS01 was efficacious and provided the strongest benefit in terms of impact against clinical and severe malaria in children aged 5-17 months at the time of the first vaccination. 16 Additionally, reductions in overall hospital admissions, admissions because of malaria, severe anemia, and the need for blood transfusion in children were observed. We also previously reported an increased risk of febrile convulsions in children vaccinated with RTS,S/AS01 in our large doubleblind, randomized, phase III trial in SSA.…”
Section: Discussionmentioning
confidence: 99%
“…The vaccine induces antibodies against parasites that have reached or are in transit to the liver (where they mature and multiply), thereby limiting the ability of the parasites to cause clinical disease. Due to the high frequency of malaria in children in some parts of the world, this vaccine has the potential to prevent a large number of malaria cases [37,38].…”
Section: Protein Vaccinesmentioning
confidence: 99%
“…The anti-malaria vaccine Malaria RTS has been certified, which represents the C-terminal part of the CS protein of Plasmodium falciparum attached to the surface antigen of the hepatitis B virus (HBsAg), which is also used in the certified vaccines against hepatitis B. To stabilize recombinant VLPs, the fused protein is expressed together with the HBsAg protein in Saccharomyces cerevisease [89]. A vaccine against the porcine circovirus representing VLPs assembled from the VP2PCV2 capsid protein synthesized in a heterologous system has also been commercialized [41].…”
Section: Commercial Vaccines Based On Vlp and Prospects Of Broadeningmentioning
confidence: 99%